Dirty work: well-intentioned mental health workers cannot ameliorate harms in offshore detention - Winters, Janine Penfield (Journal of medical ethics, 2023)
Professional providers of mental health services are motivated to help people, including, or especially, vulnerable people. We analyse the ethical implications of mental health providers accepting employment at detention centres that operate out of the normal regulatory structure of the modern state. Specifically, we examine tensions and moral harms experienced by providers at the Australian immigration detention centre on the island of Nauru. Australia has adopted indefinite offshore detention for asylum-seekers arriving by boat as part of a deterrence strategy that relies on making detainment conditions harsh. This has known deleterious mental health effects. As a token to fiduciary care obligations, Australia employs mental health professionals to work on Nauru. These providers are often motivated to make a positive difference for detainees’ lives. We examine the overall impact of the providers’ work with detainees and the implications of their presence. The strongest evidence supports that the small mitigation of harms offered by these providers does not outweigh the harms of supporting a system designed to perpetuate human suffering. For mental health professionals considering working in offshore detention, we offer specific topics to scrutinise and weigh prior to employment. Because optimising detainee’s mental health is beyond the capacity of individual providers, we call for the organisations standardising and supporting mental health professionals to oppose employment of their associates in offshore detention. Lessons from this case study are generalisable to other jurisdictions to help inform organisations that licence and support mental health providers and individual providers considering work in similar settings.